Introductory handbook on Nigerian wildlife - Ayeni, J. S. O.; Afolayan, T. A.; Ajayi, S. S.; Kainji Lake Research Institute; University of Ibadan (New Bussa, Kwara State, Nigeria : Kainji Lake Research Institute ; Ibadan, Oyo State, Nigeria : Dept. of Wildlife and Fisheries Management, University of Ibadan, 1982)
This volume describes wildlife conservation and management in Nigeria with focus on Nigeria's wild life, habitat, population dynamics, capture and hunting among others.
Errata slip inserted.
Bibliography: p. 61.
II 15/01/2019
Loans